Analisis Kandungan Logam Berat Cu dan Zn dengan Metode Spektrofotometri Serapan Atom (SSA) dalam Air Limbah Industri - Putri, Nanda Aulia; Beri, Deski (Lembaga Yasin AlSys, 2026)
Industrial wastewater is a by-product of production processes that generally has low quality because it contains various contaminants, including heavy metals, with types and concentrations depending on the characteristics of the industry that produces it. This study aims to analyze the content of copper (Cu) and zinc (Zn) metals in wastewater samples using the flame Atomic Absorption Spectrophotometry (AAS) method. This study employed a quantitative approach with a laboratory experimental design. The analysis was conducted by preparing standard solutions to obtain calibration curves as the basis for determining metal concentrations in the samples. The results show that the calibration curves had very good linearity, with coefficient of determination (R²) values of 0.9989 for Cu and 0.9956 for Zn. The concentrations of Cu metal in the samples were -0.0599 ppm and -0.0647 ppm, respectively, while the concentrations of Zn were 0.0426 ppm and -0.0072 ppm, respectively. Negative values indicate that the metal concentrations were below the detection limit of the instrument. Based on these results, the Cu and Zn contents in the wastewater samples were still below the quality standards stipulated in Regulation of the Minister of Environment of the Republic of Indonesia Number 5 of 2014, so they did not indicate a significant level of pollution. The conclusion of this study emphasizes that the flame AAS method is effective for analyzing heavy metals at low concentrations. The practical implication is that this method can be applied in monitoring industrial wastewater quality to support environmental pollution control.